PROJETO SÓ ARTE: o ensino do ballet clássico em ambiente não formal - BRITO, Márcia Cristina de Oliveira (2022)
Ballet over time goes through conceptual and structural changes in the way of teaching and working with different bodies. These who have their own unique composition. Nowadays, it can be experienced in formal and non-formal environments. We focus on analyzing ballet in non-formal environments, where classes take place in spaces that have been adapted such as: garage, cafeteria, among others. The basic theoretical framework was centered on Corrêa's studies; Araújo (2013); Oliveira (2009), Kellermann (2019), Marques (2008, 2010), Ossona (1988), Strazzacappa and Morandi (2006) Flávio Sampaio (2013), Puoli (2010), Caminada (1999, 2013) and Aragon (2013) who helped us to think about ballet and dance in different contexts. The focus of this investigation was the Centro Social Santo Agostinho in Belém / PA, specifically the Social Project Só Arte. The study aimed to analyze the ballet teaching methodology developed by the teachers. The participants were 2 (two) dance teachers from the Só Arte Project. The guiding question of the research was to know the challenges faced by the dance teacher in the non-formal environment. The study was carried out using a qualitative approach with a focus on field research. The research instruments were observation and interview, which made it possible to understand the current working conditions and the interference that this has in the teachers' pedagogical practice, which led us to reflect on the teaching methodology adopted. The results of the study showed that at the Social Center, teachers have difficulties in carrying out activities in an adapted space; Heat is another element that makes concentration difficult, due to the classes that take place in open spaces, where there is external competition of sound, voices, people moving, which affects the dynamics of teaching and learning by teachers and students and significantly interferes in the teaching-learning process of children and adolescents participating in the Só Arte Project.